1999
DOI: 10.1159/000015948
|View full text |Cite
|
Sign up to set email alerts
|

Three Years after In-Patient Stroke Rehabilitation: A Follow-Up Study

Abstract: A 3-year follow-up study was performed aimed at describing the outcome for severely affected stroke survivors who had undergone geriatric in-patient rehabilitation. Living conditions, psychological well-being, and changes in functions were assessed in 55 survivors. Twenty-five people were living in the community, 15 in apartment hotels or homes for the aged and 15 in nursing homes. From discharge to follow-up 11 people had had to move to an accommodation offering more support. Living alone, recurrent strokes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…Longitudinal studies on changes long term after stroke have thus far been scarce, 2,5,10,36,37 and most studies have concentrated on ADL outcome and mean changes. However, mean changes do not reflect individual changes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies on changes long term after stroke have thus far been scarce, 2,5,10,36,37 and most studies have concentrated on ADL outcome and mean changes. However, mean changes do not reflect individual changes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these individuals, the hemiparesis persists beyond 6 months post-stroke, limiting mobility and leading to a sedentary lifestyle. 2 The current standard of stroke care involves short-term rehabilitation therapy targeted to recovery of activities of daily living skills, after which survivors are discharged to home with exercise instructions. However, stroke survivors and their families are often too overwhelmed to focus on continued exercise beyond formal inpatient and outpatient therapies.…”
mentioning
confidence: 99%
“…8,9 Reutter-Bernays and Rentsch 8 documented a nonsignificant decline of 11% in mean BI between discharge (median time of hospitalization, 96·5 days) and several years of follow-up. Lofgren et al 9 found a significant decrease of 13% in median score on the Fugl-Meyer motor assessment between discharge from a geriatric rehabilitation unit and 3 …”
Section: Discussionmentioning
confidence: 98%